Elimination of schistosomiasis requires multifactorial diagnostics: evidence from high- and low-prevalence areas in the Nile Delta, Egypt - Hala Elmorshedy; Robert Bergquist; Amel Fayed; Wafaa Guirguis; Ensaf Abdel-Gawwad; Safaa Eissa; Rashida Barakat (BMC, 2020)
Abstract Background Schistosomiasis is one of the neglected tropical diseases (NTDs) selected for worldwide elimination in the near future. Egypt has made strong progress against its two endemic species of Schistosoma mansoni and S. haematobium. The former is prevalent in the Nile Delta with the latter dominating in the Nile south of Cairo. Innovative efforts are needed to reach the goal as further reduction of the prevalence has stalled due to ongoing transmission. In this study we aimed to explore the difference between low and high prevalence villages with regard to knowledge attitude and practice about schistosomiasis, utilization of health services, infection and transmission indices. Methods A hybrid cross-sectional longitudinal study was conducted with three annual follow-ups conducted during 1994-1996. We used a representative systematic random sampling technique investigating 993 individuals from the high prevalence village and 614 from the low prevalence village. Data were analyzed using SPSS, comparing proportions with the Chi square test and means with the Student t test, and ANOVA. Results Compliance of faecal sampling and chemotherapy was above 70% in both villages over the whole study period. Selective praziquantel treatment resulted in a significant reduction of prevalence and intensity of infection in both villages, dropping from 35.8% prevalence to 20.6%, in the low-prevalence village, and from 69.5 to 45.9% in the high-prevalence one. Intensity of infection at the base line was 30 eggs per gram (EPG) of stool in the low-prevalence village versus 105 EPG in the high-prevalence village. However, after the second round, reinfection rebounded by 22% in the high-prevalence village, while a slight improvement of the infection indices was demonstrated in the low-prevalence one. The level of knowledge was modest in both villages: people knew about self-protection and treatment, but not much about the role of human excreta for schistosomiasis transmission. While all participants maintained that using the water from the canals was inevitable, inhabitants in the high-prevalence village showed significantly lower scores reflecting higher water contact compared to the low-prevalence one. Many of them (67%) did not utilize the health centre at all compared to 26% of the people in the low-prevalence village. Interestingly, private clinics were seen as the primary source of health care by both villages, but more frequently so in the high-prevalence village (used by 87.2% of the inhabitants) compared to the low-prevalence one (59.8%). Conclusions Even if chemotherapy works well as reflected by the observed downregulation of intensity of infection in both villages, reinfection continued due to difficulties to avoid water contact. Efforts must be made to make people understand the role of human excreta for transmission. There is also a need to make people better trust the medical services available.